2016
DOI: 10.1007/s10508-016-0751-1
|View full text |Cite
|
Sign up to set email alerts
|

“The Pleasure Is Better as I’ve Gotten Older”: Sexual Health, Sexuality, and Sexual Risk Behaviors Among Older Women Living With HIV

Abstract: There is limited research examining the sexual health and wellbeing of older women living with HIV (OWLH). Most studies focus on sexual dysfunction, leaving aside the richer context of sexuality and sexual health, including the effect of age-related psychosocial and interpersonal changes on sexual health behaviors. Guided by the integrative biopsychosocial model and the sexual health model, this study explored the importance of sex and sexuality among OWLH to identify their sexual health and HIV prevention nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 78 publications
1
26
0
Order By: Relevance
“…41 Condom use may be difficult for older women to negotiate for many reasons, including psychosocial concerns that affect women of all ages (relationship dynamics and trust) and concerns that older women more commonly have (men with erectile dysfunction may have difficulty with condom use, adherence to traditional ideas of sex and power in relationships). 42,43 It is important to counsel older women about specific strategies for safer sex, including strategies to encourage their partners to use condoms.…”
Section: Approach To Casementioning
confidence: 99%
“…41 Condom use may be difficult for older women to negotiate for many reasons, including psychosocial concerns that affect women of all ages (relationship dynamics and trust) and concerns that older women more commonly have (men with erectile dysfunction may have difficulty with condom use, adherence to traditional ideas of sex and power in relationships). 42,43 It is important to counsel older women about specific strategies for safer sex, including strategies to encourage their partners to use condoms.…”
Section: Approach To Casementioning
confidence: 99%
“…Such pleasures are important for overall health; ii) sex is an important biological and biopsychological function, and everyone has the ability to feel sexual pleasure; iii) sexual pleasure is everyone's right; iv) all humans deserve sexual satisfaction; and v) the experience of sexual satisfaction (sexual fulfillment) is important for the emotional and physical well-being, independent of age and some health conditions. 51,52 The learning session allows the gynecologist to deal with sexual myths and mistaken beliefs about sex, and to reformulate concepts on affectivity and the sharing of sexual experiences. 53 Successful treatment of sexual complaints suggests that the enjoyment of sexuality increases after women learn that sexuality is healthy.…”
Section: Permitting (P) and Stimulating Sexual Pleasurementioning
confidence: 99%
“…An analysis of data from the US Women's Interagency HIV Study found that women living with HIV were more likely to report sexual impairment compared to women without HIV, across all age groups (Wilson et al, 2010). Qualitative data reveal the importance of sexual pleasure for older women living with HIV, with diminished libido and vaginal dryness highlighted as particularly important (Taylor et al, 2017). Data on sexual function in older women living with HIV remain limited, and mainly originate from the US or Brazil.…”
Section: Introductionmentioning
confidence: 99%